Thai Language Usage in Naming Indian Film - Udom, Sittigun; Mahabunyakorn, Warinthorn; Cherngchawano, Kotchabhorn; Punted, Thamonwan; Detmak, Wanvisa; Pimpuang, Kowit (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
Throughout a study of Thai language usage in naming Indian film, the objectives of this research were to study the use of Thai words in naming Indian film titles and to study the strategies in giving Indian films titles. For this study, 148 film titles were selected and used from a wide selection of 240 films through the purposive sampling from B.E. 2520-2559. It was found that there were a total of the nine different characteristics of the Thai language used in order to name Indian film titles namely; Connotative and comparative words, wordplay, transliteration, modifier, new word, compound word, interjection, additional word and onomatopoeia. Connotative and comparative words are found to be the most frequently used characteristics, followed by wordplay, transliteration, modifier, new word, compound word, interjection, additional word and onomatopoeia. Regarding the strategies in giving Indian films titles, the following there are different strategies; the content of the films, the main characters of the movies, and the significance of objects and places are found. The content of the films (storyline) are found to be the most frequently used strategies, followed by the main characters of the films, and the significance of objects and places.